Spaceborne LiDAR-derived height-variable forest wind reduction factors (WRF) for improved wildfire spread modelling - Molly A. Harrison; Philip J. Noske; Christopher S. Lyell; Kangmin Moon; Darcy P. Prior; Gary J. Sheridan; Thomas Keeble (Agricultural and Forest Meteorology, 2025)

Non-native vegetation encroachment drives trophic turnover in island nematodes - Adam Sharp; Margarida Correia; Alan Gray; Rebecca Lawson; Martha Ledger; Noel Tawatao; Thomas Prior (Biodiversity and Conservation, 2025)
Nematodes are important components of terrestrial ecosystems. There is currently limited understanding of how soil nematode communities are altered by non-native vegetation encroachment. The spatial turnover of nematode communities was studied on Ascension Island in the South Atlantic: an isolated and degraded volcanic island of sparse native vegetation. Many non-native plants were introduced in the mid-1800’s, and non-native shrubs have more recently spread across the lowlands. Ascension’s elevation gradient represented a unique space-for-time proxy for non-native vegetation colonisation of a relatively barren landscape. Nematodes were collected at 0, 200, 400, 600 and 800 m elevations along three transects and their community composition linked to Landsat-derived vegetation cover and moisture over the 2000–2023 period. Although taxonomic turnover was elevation independent, both nematode abundance and richness increased with elevation. The moist and densely-vegetated mountain top was dominated by plant-root parasites, less dense mid-elevations by omnivores, dry and sparsely-vegetated lowlands by fungivores, and the moist littoral habitat by predators. Landsat analysis predicted that the relative abundance of root parasitic nematodes on Ascension increased by 23% with spreading non-native vegetation over 24 years. While taxonomic turnover in nematode composition may be resultant solely of historic species introductions, trophic turnover is spatially structured and likely follows non-native vegetation encroachment closely. Root parasitic nematodes may be spreading rapidly with non-native vegetation, especially on oceanic islands. The abundance of such nematodes in soil could become an unanticipated hinderance in the restoration of invaded habitat – potentially requiring management long after non-native vegetation is cleared.

The use of recovery animals in nonclinical safety assessment studies with monoclonal antibodies: further 3Rs opportunities remain - Helen Prior; Laura Andrews; Annick Cauvin; Hsiaotzu Chien; David O. Clarke; Kaushik Datta; Maggie Dempster; Noel Dybdal; Wendy Freebern; Lolke de Haan; Danuta Herzyk; Adam Hey; et al. (Regulatory Toxicology and Pharmacology, 2023)

Re-evaluating the need for chronic toxicity studies with therapeutic monoclonal antibodies, using a weight of evidence approach - Hsiao-Tzu Chien; Helen Prior; Laura Andrews; Leon van Aerts; Annick Cauvin; David O. Clarke; Kaushik Datta; Maggie Dempster; Noel Dybdal; Wendy Freebern; Lolke de Haan; Danuta Herzyk; et al. (Regulatory Toxicology and Pharmacology, 2023)

Complete sequencing of the SMN2 gene in SMA patients detects SMN gene deletion junctions and variants in SMN2 that modify the SMA phenotype - Corey Ruhno; Vicki L. McGovern; Matthew R. Avenarius; Pamela J. Snyder; Thomas W. Prior; Flavia C. Nery; Abdurrahman Muhtaseb; Jennifer S. Roggenbuck; John T. Kissel; Valeria A. Sansone; Jennifer J. Siranosian; Alec J. Johnstone; et al. (Human Genetics, 2019)

An integrative approach to the study of Xiphinema brevicolle Lordello and Da Costa 1961, supports its limited distribution worldwide (Nematoda: Longidoridae) - Stela Lazarova; Claudio Marcelo G. Oliveira; Thomas Prior; Vlada Peneva; Shesh Kumari (European Journal of Plant Pathology, 2019)

Insights from community ecology into the role of enemy release in causing invasion success: the importance of native enemy effects - Kirsten M. Prior; Thomas H. Q. Powell; Ashley L. Joseph; Jessica J. Hellmann (Biological Invasions, 2015)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Opposite association of two PPARG variants with cancer: overrepresentation of H449H in endometrial carcinoma cases and underrepresentation of P12A in renal cell carcinoma cases - Wendy Smith; Xiao-Ping Zhou; Keisuke Kurose; Xin Gao; Farida Latif; Todd Kroll; Kokichi Sugano; Stephen Cannistra; Steven Clinton; Eamonn Maher; Thomas Prior; Charis Eng (Human Genetics, 2001)

Biarticular and monoarticular muscle activation and injury in human quadriceps muscle - Barry M. Prior; Roop C. Jayaraman; Robert W. Reid; Thomas G. Cooper; Jeanne M. Foley; Gary A. Dudley; Ronald A. Meyer (European Journal of Applied Physiology, 2001)

Hybrids monosomal for human chromosome 5 reveal the presence of a spinal muscular atrophy (SMA) carrier with two SMN1 copies on one chromosome - Matthew Mailman; Tamara Hemingway; Rebecca Darsey; Carol Glasure; Ying Huang; Robert Chadwick; John Heinz; Audrey Papp; Pamela Snyder; Mary Sedra; Robert Schafer; Dianne Abuelo; et al. (Human Genetics, 2001)